Delayed hypersensitivity reaction secondary to intraperitoneal vancomycin administration - Zakaria, NF; Premila, AA; Shah, A (The Ministry of Health and Universiti Brunei Darussalam, 2023)
Vancomycin has been a drug of choice for infections with a broad range of Gram-positive bacteria. Intraperitoneal (IP) Vancomycin is used to treat methicillin-resistant staphylococcal peritonitis, administered intermittently at 3 to 5 days intervals with trough level monitoring. Numerous adverse drug reactions (ADRs) have been reported with intravenous usage; however, the ADRs are not well known in intraperitoneal administration. We report a case of a delayed hypersensitivity reaction following intraperitoneal vancomycin administration. To date, this is the second case with a similar incidence.